Cyclosporin for the treatment of severe inflammatory bowel disease. - Baker, K; Jewell, D (1989)
A pilot study was performed to assess the role of cyclosporin in the management of severe inflammatory bowel disease. Twelve patients with Crohn's disease and 12 with ulcerative colitis were admitted to hospital with a severe attack. They were treated with an intravenous regimen of corticosteroids for 5 days followed by oral therapy. In addition, they received a 6-week course of oral cyclosporin, initially 15 mg kg-1 day-1 reduced to 7.5 mg kg-1 day-1. In comparison with historical controls, the addition of cyclosporin to standard corticosteroid therapy appeared to have no benefit. Adverse effects were common but minor. The expression of Class II molecules on the inflamed epithelium was rapidly reversed by cyclosporin therapy which may indicate a potential therapeutic benefit over longer periods of time.